Pengetahuan dan Sikap Mahasiswa dalam Keputusan Pembelian Produk Halal - Ali Rosidi; Tatik Musdianingwati; Agus Suyanto; Muh Yusuf; Enik Sulistyowati (Universitas Muhammadiyah Semarang, 2018)
Consumers must be more critical in making decisions before buying food products. This study aims to determine the relationship between knowledge with student attitudes in purchasing decisionsfor halal products. The population of this study were the students of Muhammadiyah University ofSemarang. The variables that studied were the level of knowledge of halal food and the attitude ofdecisions for buying halal products. This type of research was observational with a cross sectionaldesign. The tool that used were questionnaires and data analysis by using two stages, namelyunivariate and bivariate (Simple Linear Regression). The results of the study revealed that thestudent's knowledge of halal food was the most moderate category at 40.2% and positive positiveattitude was 53.6%. Based on statistical tests, it can be concluded that there is a relationship betweenknowledge and attitude in buying halal products.Keywords: Halal, Product, Knowledge, Attitude.